Espirais I e II de Almeida Prado: relações entre os dois ciclos de canções escritas a partir dos mesmos poemas - Yangmei Hon (2018)
Espiral (1985) and Espiral II (1993) are two cycles of ten songs each for voice and piano written by the composer Almeida Prado (1943-2010). Both were composed over the same poems written by José Aristodemo Pinotti (1934-2009). The tittles set to music by Almeida Prado were: Através do Canal, Valéry, Café de la Paix, Tua boca mágica, Antropologia, Dia seguinte, Síntese, Começo, Fragmento and Espiral. The main objective of this work is to make a comparative analysis of the cycles songs from Espiral and Espiral II, by transcribing the melodic profiles of each song into diagrams developed by professor Luiz Tatit (TATIT, 1986). We therefore try to demonstrate a methodological indicative of study based mainly on the melodic direction of each phrase of the songs. Considering also the importance of the "landscape accompaniment" (ALMEIDA PRADO, 2013a) performed by the piano, with the influence of parameters such as rhythm, harmony, texture and dynamics in performance construction, this work uses methods outlined by professor Dante Grela (GRELA, 1986) to emphasize the findings of melodic analysis and even add new information about each song. This study may allow a better understanding and interpretation of the composer's musical choices in both cycles, and may also provide subsidies for the construction of an authentic performance for each song.